GOOD CORPORATE GOVERNANCE IN MICRO AND SMALL BUSINESS TAKES INTERNATIONALISATION? - Domingues, Luciana Madureira; Muritiba, Patricia Morilha; Muritiba, Sergio Nunes (Contextus - Revista Contemporânea de Economia e Gestão, 2016)
In small and medium enterprises, the ownership structure is formed by few shareholders, which makes it more difficult to investors and stakeholders to evaluate the of the corporate governance quality. This study presents a novel perspective to aid to this problem: we use Gubitta and Gianechini’s (2002) model, that classifies SMEs’ corporate governance into open or closed categories, according to the level in which independent members (such as boards of directors, professional managers or management consultants) support stakeholders in decision making. We investigate the relationship between governance and SME’s internationalization. This is an important effect of governance, since many SMEs in Brazil suffer great deal of pressure from global players such as China and India. We collected quantitative data with 41 Brazilian SMEs. Results showed that companies with a more open corporate governance system are more proactive in regards to internationalization than the ones with closed governance systems.